Epidemiology of Measles and Rubella in Yogyakarta City 2013-2022 - Sulistyani, Dwi Ana; Solikhah, Solikhah; Sulistyawati, Sulistyawati (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Introduction: Measles and Rubella are still a public health problem in Indonesia, including in Yogyakarta. Extraordinary Measles and Rubella Incidents in the City of Yogyakarta are still being reported. In 2022, there will be 2 cases. Nevertheless, measles and Rubella have a high potential for transmission, death and cause more severe complications. This study aims to determine the trend of measles and Rubella cases in Yogyakarta from 2013-2022. Methods: This study used a descriptive research design. Data on measles and rubella cases were taken from the Yogyakarta City Health Office Case Based Measles Surveillance (CBMS) report for 2013-2022.Results: Measles and Rubella cases tend to decrease in 2018-2021 and increase again in 2022. Of the 2928 suspected measles, the majority were women (50.8%) and aged over 15 years. There were 459 confirmed cases of measles and 468 instances of Rubella. Of the two cases of measles and Rubella, most suffered from children. Conclusion: Laboratory-confirmed incidences of measles and rubella are found in all areas of the subdistrict and are more prevalent in children. Strengthening the body's resistance and immunity to measles-rubella infection must be done to prevent measles-rubella outbreaks with transmission in the school environment. Keywords: Measles, Rubella, Surveillance, Yogyakarta City